2021
DOI: 10.1080/13510002.2021.1962094
|View full text |Cite
|
Sign up to set email alerts
|

Current evidence to support the therapeutic potential of flavonoids in oxidative stress-related dermatoses

Abstract: Background: Skin, as a crucial external defense organ, is more vulnerable to oxidative stress (OS) insult, reactive oxygen species (ROS)-mediated OS in particular. OS results from a redox imbalance caused by various extrinsic stimuli and occurs once the oxidants production overwhelming the antioxidants capacity, through mediating in DNA damage, lipid peroxidation (LPO), protein oxidation and a serial of signaling pathways activation/inactivation, thereby offering favorable conditions for the occurrence and dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 150 publications
0
14
0
Order By: Relevance
“…It has also been revealed that flavonoids exert an antiskin photoaging effect [ 10 ]. Xian et al [ 11 ] showed that flavonoids could reduce skin photodamage via various mechanisms such as inhibiting inflammation, scavenging free radicals, combatting oxidation, preventing DNA damage, and maintaining the normal synthesis and degradation of ECM in the skin. Flavonoids added in cosmetics can absorb UVA and UVB with wavelengths of 200–400 nm and have antiphotoaging effects by regulating sunburn signaling pathways [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been revealed that flavonoids exert an antiskin photoaging effect [ 10 ]. Xian et al [ 11 ] showed that flavonoids could reduce skin photodamage via various mechanisms such as inhibiting inflammation, scavenging free radicals, combatting oxidation, preventing DNA damage, and maintaining the normal synthesis and degradation of ECM in the skin. Flavonoids added in cosmetics can absorb UVA and UVB with wavelengths of 200–400 nm and have antiphotoaging effects by regulating sunburn signaling pathways [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence for the preventive potential of luteolin in skin cancers associated with, inter alia skin photodamage as well as Nrf2 activity, closely related to oxidative stress. Luteolin suppresses the expression of COX‐2, AP‐1, and NF‐κB, regulates antioxidant enzymes, and prevents ROS accumulation and activation of MAKP and NF‐κB signaling pathways 207 . The antioxidant activity of luteolin is a partial contribution to its anti‐inflammatory effect, which is also related to the prevention of the carcinogenesis process due to the convergence of chronic inflammation and cancer 45,56 .…”
Section: Bioactivity Of Luteolin and Its Derivatives On Skin Cancermentioning
confidence: 99%
“…Luteolin suppresses the expression of COX‐2, AP‐1, and NF‐κB, regulates antioxidant enzymes, and prevents ROS accumulation and activation of MAKP and NF‐κB signaling pathways. 207 The antioxidant activity of luteolin is a partial contribution to its anti‐inflammatory effect, which is also related to the prevention of the carcinogenesis process due to the convergence of chronic inflammation and cancer. 45 , 56 This luteolin effect is mediated by cells such as neutrophils and lymphocytes; TNF‐α and IL‐6 release‐related inhibition; and signaling pathways involving these factors as previously described.…”
Section: Bioactivity Of Luteolin and Its Derivatives On Skin Cancermentioning
confidence: 99%
“…It is used in the treatment and care of oily and polluted skin. Common nettle rich in quercetin, rutin and kaempferol is used as an external compress in case of seborrhea and inflammation [1,15,16]. By combining the above natural therapies, very good therapeutic effect can be achieved with less strain on the body.…”
Section: Psoriasismentioning
confidence: 99%